Islamization of Management Accounting and Business Decision-Making: A Literature Review - Md Sajid Hasan; Sheikh Abu Toha Md Saky; Md. Nurul Islam (Bulletin of Islamic Research, 2026)
Conventional management accounting systems have largely evolved within Western economic paradigms that emphasize profit maximization, efficiency, and shareholder primacy. While these models have enhanced organizational performance, they have also been widely criticized for their ethical limitations, short-term orientation, and neglect of broader social and moral responsibilities in business decision-making. In response to these concerns, the Islamization of Knowledge (IoK) offers an alternative intellectual framework that integrates Islamic epistemology and ethical principles into modern disciplines. This study adopts a narrative and integrative literature review approach to examine the Islamization of management accounting and its implications for business decision-making. Drawing on conceptual, theoretical, and empirical literature, the review synthesizes Islamic principles such as Tawhid (unity of God), Amanah (trust), Adl (justice), Maslahah (public interest), and Hisab (accountability) and analyzes their relevance to planning, control, performance measurement, and managerial decision processes. The findings reveal that Islamized management accounting redefines accounting information as a moral and ethical instrument that supports accountability beyond shareholders, promotes social justice, and emphasizes long-term societal welfare. The study contributes to accounting and business ethics literature by providing a conceptual foundation for Islamized management accounting and identifying key research gaps, including the absence of comprehensive frameworks and empirical evidence. Future research directions for developing practical Islamized management accounting models are also proposed.